Computer and cyber security principles, algorithm, applications, and perspectives - Gupta, Brij; Wang, Haoxiang; Agrawal, Dharma P. (CRC Press, Taylor & Francis Group, 2019)
This is a monumental reference for the theory and practice of computer security. Comprehensive in scope, this text covers applied and practical elements, theory, and the reasons for the design of applications and security techniques. This book is acclaimed for its scope, clear and lucid writing, and its combination of formal and theoretical aspects with real systems, technologies, techniques, and policies.